The index of impulsive periodic orbits. (March 2020) - Ding, Boyang; Pan, Shiyao; Ding, Changming
Abstract: In this paper, we introduce the index of an impulsive periodic orbit, which can be used to judge the Zhukovskiǐ quasi-stabilities of periodic orbits. Also, we present an example of predator–prey model to illustrate our results.